Open Surgery for Patellar Tendon Rupture and Tibial Tuberosity Avulsion Fracture in Pre-Existing Osgood Schlatter Lesion: A Case Report - Shianita Limena; Anak Agung Ngurah Ronny Kesuma; I Komang Mahendra Laksana (Journal Orthopaedi and Traumatology Surabaya, 2021)
Background: In Osgood Schlatter Disease, despite being a self-limiting disease during adolescence, various complications of Osgood Schlatter Disease could also present in adulthood. An uncommon injury pattern requires surgical treatment. This study aims to understand the implementation of surgery in managing complications case of Osgood Schlatter Disease.Case Report: We present a rare case of complete patellar tendon rupture and tibial tuberosity avulsion fracture following a low-energy motor vehicle accident landing on his left knee in a 42 years old active male, who later discovered is having a pre-existing Osgood Schlatter Disease. This patient is treated with an open surgery fixating the tibial tuberosity using a single lag screw and eight tension wires, followed by primary repair of the patellar tendon, including its retinaculum.Discussion: Weakened structure from pre-existing Osgood Schlatter lesion may cause uncommon and profound injury pattern that requires surgical treatment. Conservative treatment no longer has a place in this case. The various surgical treatment methods have been reported; however, surgical modification technique is performed accordingly due to the complicated case presentation.Conclusion: Surgical treatment is the most suitable treatment option in managing this uncommon injury pattern complication of Osgood Schlatter Disease.